Activation pattern of neutrophils from blood of elderly individuals with Candida-related denture stomatitis - Gasparoto, T. H.; de Oliveira, C. E.; Vieira, N. A.; Porto, V. C.; Cunha, F. Q.; Garlet, G. P.; Campanelli, A. P.; Lara, V. S. (European journal of clinical microbiology & infectious diseases, 2012)
We have identified impaired neutrophils in elderly individuals which could be involved with Candida -related denture stomatitis (DS), an oral infection predominantly caused by Candida albicans , affecting especially elderly individuals using dental prosthesis. However, specific mechanisms performed by neutrophil contributing to the susceptibility of the elderly to DS are not fully understood. This study evaluated activation features of blood neutrophils from elderly and young individuals with DS. Blood neutrophils cultured with C . albicans from elderly subjects secreted decreased levels of CXCL8. However, C . albicans challenged-neutrophils from DS patients produced high IL-4 and IL-10, and low GM-CSF levels, regardless of age. Additional elastase activity of neutrophils from both elderly groups was detected after incubation with C . albicans , but only neutrophils from elderly DS demonstrated high myeloperoxidase activity. Therefore, DS patients have affected neutrophils, and the advance of age intensifies these damages. In sumamry, individuals with Candida -related denture stomatitis presented variation in the neutrophil phenotype and activation. Such alterations were more intense in neutrophils from infected elderly individuals.